2014
DOI: 10.5966/sctm.2014-0070
|View full text |Cite
|
Sign up to set email alerts
|

Xiphoid Process-Derived Chondrocytes: A Novel Cell Source for Elastic Cartilage Regeneration

Abstract: Reconstruction of elastic cartilage requires a source of chondrocytes that display a reliable differentiation tendency. Predetermined tissue progenitor cells are ideal candidates for meeting this need; however, it is difficult to obtain donor elastic cartilage tissue because most elastic cartilage serves important functions or forms external structures, making these tissues indispensable. We found vestigial cartilage tissue in xiphoid processes and characterized it as hyaline cartilage in the proximal region a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
5
0
3
Order By: Relevance
“…Analysis of the In Vitro Differentiation Potential : Differentiation to one of three different lineages—adipogenesis, osteogenesis, and chondrogenesis—was induced, as described previously . Briefly, BMSCs were plated on cover slips or 2.5D microcarriers and were cultured to 90% confluence before inducing differentiation.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of the In Vitro Differentiation Potential : Differentiation to one of three different lineages—adipogenesis, osteogenesis, and chondrogenesis—was induced, as described previously . Briefly, BMSCs were plated on cover slips or 2.5D microcarriers and were cultured to 90% confluence before inducing differentiation.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, cartilage regeneration currently is still a worldwide challenge [ 20 , 21 ]. Among the different types of cartilage, XC can be obtained conveniently, and has a potential capacity for cartilage reconstruction due to its expansion and differentiation characteristics, and it has been widely used as a tissue model for investigation cartilage injury and repair [ 22 24 ]. Furthermore, it has been shown that XC contains cartilaginous tissue with a similar histological structure to that of articular cartilage, and histological and metabolic changes in murine XC are similar to those in articular cartilage after mechanical injury [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Discerning the difference of pathophysiology in animal model is very important because research focus of regenerative medicine puts weight not only on reconstructive therapeutic regimen [7][8][9][10] but also preventive strategy before or at the onset of disease progression [11][12][13][14][15][16][17]. Therefore, understanding the subtle difference of disease mechanism and realization of rightful animal model is very important in the investigation of the therapy.…”
Section: Introductionmentioning
confidence: 99%